Sustainable Livelihood Conditions of Farm Worker Households around Baluran National Park: Case Study in Wonorejo, Indonesia - Sri Rahayu Budiani; Ratri Purnama Dewi; Kurniawati Kurniawati; Tiara Putri Amalia; Monita Deka Pratiwi; Retno Murti Andayaningrum; Ulil Usnaini; Putri Dwi Yuliana (Populasi, 2021)
Farm workers are a group that is vulnerable to poverty and depends on weather or climatic factors. However, this profession dominates one of the villages around the Baluran National Park of Indonesia, i.e., Wonorejo, Banyuputih Subdistrict, Situbondo District, East Java. The Baluran National Park is a natural resource conservation area with a savanna ecosystem that was established in March 1980 through the Deklarasi Lima Taman Nasional (Declaration of Five National Parks) of Indonesia. It has an area of 25,000 hectares located in Banyuputih Subdistrict, Situbondo District, East Java and includes t h ree villages, i.e., Wonorejo, Sumberwaru, and Sumberanyar. This study aimed to describe the sustainable livelihood conditions of farm worker households in Wonorejo. This study is a quantitative research through household surveys and is supported by in-depth interviews with expert informants. The results of this study confirmed that farm workers in Wonorejo had good access to five livelihood assets, i.e., natural, physical, human, social, and financial assets. They had also been able to survive without destroying the natural resources in Baluran National Park.